Significance of Chinese Travelogues as Historical Sources - Gnawaly, Bikash (Journal of Buddhist Studies (T.U.), 2025)
This study explores the significance of Chinese travelogues in the context of Nepal studies, emphasizing their underutilized potential in contemporary research. While these travelogues have traditionally been referenced in the historical and archaeological analysis of Buddhist sites in Nepal, their broader relevance in understanding Nepal’s cultural, ethnic, religious, economic, geopolitical, and geographical history has not been critically examined. This paper argues that these travelogues, despite containing a mix of authentic and inconsistent information, hold multidisciplinary value when subjected to rigorous verification. Through textual analysis, the study highlights how these records can address existing knowledge gaps and contribute to a deeper understanding of Nepal’s historical roots and transnational connections.